Implementasi Metode Klasifikasi ABC pada Warehouse Management System PT. Cakrawala Tunggal Sejahtera - Ivan Chatisa; Istianah Muslim; Rika Perdana Sari (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
Warehouse is a place used to store and put items owned by company. There are many activities carried out in the warehouse, starting from data collection process to management of the items. However, there are still companies that have difficulty in collecting data and management of available items. As the process of collecting goods is still done manually, it takes a long time to find information from the item. Therefore, a Warehouse Management System (WMS) was built by implementing the ABC classification method to help the company in managing items at the warehouse. ABC classification method is a method used to group items into certain classes based on the annual demand of the item. This method is used to regulate the placement of items in the warehouse. After the ABC method is implemented on the system, the company is able to to arrange the items and to obtain the information of the most needed items by consumers easier. The result of User Acceptance Test (UAT), which was conducted 3 times, states that all of user needs have been fulfilled and accepted entirely. Then, based on the results of the questionnaire recapitulation distributed to employees as many as 30 respondents, it is obtained that as many as 91.33% of respondents state that the system is easy to use and provides complete and accurate information (strongly agree).